The Digital Paradox: Doom Spending, Algorithmic Exploitation, and the Imperative for a Maqāṣid al-Sharīʿah Framework in the Digital - Uke Cahya Ningrum; Nikmatul Masruroh; Siti Masrohatin (Eastasouth Institute, 2026)
The accelerating digitalization of global economic activity has created a complex ethical landscape, presenting simultaneous challenges in consumer behavior and labor welfare. This article addresses two distinct yet interlinked crises emerging within this digital sphere: doom spending, defined as impulsive, stress-induced consumption resulting in financial and psychological distress, and gig worker precarity, characterized by job insecurity, income volatility, and potentially exploitative algorithmic control within platform economies. Existing scholarship often analyzes these issues separately, utilizing either psychological or secular economic frameworks. This research bridges this gap by employing the holistic ethical framework of Maqāṣid al-Sharīʿah (the objectives of Islamic law) to provide a unified analysis. This framework mandates the protection of five core necessities (al-kulliyyāt al-khams): religion (dīn), life/self (nafs), intellect (‘aql), lineage/dignity (nasl/’ird), and property/wealth (māl). Findings synthesized from psychological, economic, and Islamic ethics literature demonstrate that doom spending inherently violates ḥifẓ al-māl through extravagance (isrāf/tabdhīr) and ḥifẓ al-nafs by exacerbating mental distress. Simultaneously, algorithmic management in the gig economy conflicts with Maqāṣid principles by undermining worker dignity (ḥifẓ al-‘ird), threatening safety (ḥifẓ al-nafs) through high-risk incentives, and denying fair, transparent compensation (ḥifẓ al-māl). The study proposes that a Maqāṣid-informed governance model is essential for regulating the digital economy. Recommended interventions include promoting faith-informed virtues like moderation (wasatiyyah) and contentment (qana’ah) to combat consumerism, and implementing Sharia-compliant social protection instruments (e.g., specialized takaful schemes) and algorithmic transparency mechanisms to safeguard gig worker financial stability and ethical dignity. Ultimately, the integration of Maqāṣid al-Sharīʿah offers a rigorous ethical compass, ensuring that digital economic activity promotes genuine well-being (al-falāḥ) and comprehensive social justice.